Cephalosporin antibiotics in the aquatic environment: A critical review of occurrence, fate, ecotoxicity and removal technologies. (October 2018) - Ribeiro, Alyson R.; Sures, Bernd; Schmidt, Torsten C.
Abstract: Due to their widespread occurrence in the aquatic environment, human and veterinary cephalosporin antibiotics have been studied as water pollutants. In order to characterize environmental risks of this compound class, this review evaluates relevant data about physicochemical properties, occurrence, ecotoxicity and degradation of cephalosporins. Although application of cephalosporins is rather low compared to other antibiotics and their environmental life-time is believed to be short (i.e. days), the available data is insufficient to draw conclusions on their environmental relevance. Few studies concerning the fate of cephalosporins in soil are available, while hydrolysis and photo-degradation are suggested as the main attenuation processes in the aquatic environment. Cephalosporins have been detected in different aqueous matrices in concentrations ranging from 0.30 ng L −1 to 0.03 mg L −1, with sewage and wastewater being the main matrices with positive findings. For wastewater treatment purposes, several technologies have been tested for the abatement of cephalosporins, including photolysis and adsorption. In most cases, the technology employed led to complete or significant removal (>95%) of parental drugs but few authors reported on cephalosporins' metabolites and transformation products. Furthermore, the present ecotoxicological data are insufficient for comprehensive ecological risk quotient calculations. Considering the total of 53 cephalosporins, effective values (EC, LC, NOAEC, NOAEL, etc.) are only available for around 30% of parental drugs and are very scarce for cyanobacteria, which is considered to be the most sensitive group of organisms to antibiotics. Furthermore, it has been demonstrated that cephalosporins' transformation products can be more toxic and more persistent than the parental drugs. Few investigations considering this possibility are available. Consequently, more effort on ecotoxicological data generation and verification of biological inactivation of cephalosporins-related products is needed. Likewise, the lack of natural depletion rates and knowledge gaps on mixture effects for cephalosporins' degradation and toxicity have to be overcome. Graphical abstract: Highlights: Information on cephalosporins' release, transformation and ecotoxicity is too limited. Abiotic processes are of fundamental importance for cephalosporins' environmental fate. Response studies of aquatic organisms have to include transformation products. Abstract : Environmental fate and effects of cephalosporin antibiotics need to be studied in more detail in the future including abiotic transformation products.